问题 解答题
计算,能简算的要简算.
5
6
-
3
10
+
5
6
-
7
10
=

11
8
-(
5
6
+
3
8
)=

5
9
-(
2
9
-
1
5
)=
6
7
-(
11
14
-
1
2
)=
5
9
+
4
11
+
6
11
+
4
9
=
5
7
+
1
4
-
5
7
=
答案

(1)

5
6
-
3
10
+
5
6
-
7
10

=(

5
6
+
5
6
)-(
3
10
+
7
10
),

=

5
3
-1,

=

2
3

(2)

11
8
-(
5
6
+
3
8
),

=

11
8
-
5
6
-
3
8

=(

11
8
-
3
8
)-
5
6

=1-

5
6

=

1
6

(3)

5
9
-(
2
9
-
1
5
),

=

5
9
-
2
9
+
1
5

=

1
3
+
1
5

=

8
15

(4)

6
7
-(
11
14
-
1
2
),

=

6
7
-
2
7

=

4
7

(5)

5
9
+
4
11
+
6
11
+
4
9

=(

5
9
+
4
9
)+(
4
11
+
6
11
),

=1+

10
11

=1

10
11

(6)

5
7
+
1
4
-
5
7

=(

5
7
-
5
7
)+
1
4

=

1
4

单项选择题
单项选择题